Simulation, implementation and measurement of defined sound fields for blood-brain barrier opening in rats: original contribution - Grudzenski-Theis, Saskia; Heger, Stefan; de Jonge, Andreas; Schipp, Julia; Dumont, Erik; Larrat, Benoit; Schad, Lothar R.; Platten, Michael; Fatar, Marc (Ultrasound in medicine & biology, 2022)
The blood-brain barrier (BBB) is the most important obstacle to delivery of therapeutics to the central nervous system. Low-intensity pulsed focused ultrasound (FUS) in combination with microbubbles applied under magnetic resonance imaging (MRI) control provides a non-invasive and safe technique for BBB opening (BBBo). In rodent models, however, settings and application protocols differ significantly. Depending on the strain and size, important variables include ultrasound attenuation and sound field distortion caused by the skull. We examined the ultrasound attenuation of the skull of Wistar rats using a targeted FUS system. By modifying the transducer elements and by varying and simulating the acoustic field of the FUS system, we measured a skull attenuation of about 60%. To evaluate potential application of the targeted FUS system in genetically modified animals with increased sensitivity to brain hemorrhage caused by vascular dysfunction, we assessed safety in healthy animals. Histological and MRI analyses of the central nervous system revealed an increase in the number and severity of hyperacute bleeds with focal pressure. At a pressure of 0.4 MPa, no bleeds were induced, albeit at the cost of a weaker hyperintense MRI signal post BBBo. These results indicate a relationship between pressure and the dimension of permeabilization.
Online verfügbar: 2. Dezember 2021, Artikelversion: 4. Februar 2022
Gesehen am 23.04.2024